THE EFFECTIVENESS OF USING STORYTELLING IN IMPROVING SPEAKING SKILLS FOR B1 LEVEL STUDENTS (INTERMEDIATE) - Muzaffarova Rakhima; Isroilova Sogdiana (Western European Studies, 2024)
This article discusses a variety of advantages of telling stories, such as genuine and enhanced language input, resulting in genuine language output by allowing them to structure the information from the stories in their own unique way based on their own experiences.
Keywords: students; language; English; speaking